Enhancing Procurement Efficiency Through E-Purchasing Methods - Rakhmat Dwi Pambudi (Green Economics Review, 2024)
E-purchasing has been integrated into government procurement processes for over a decade, revolutionizing how goods and services are acquired. This study explores the implementation of e-purchasing at UIN Walisongo Semarang, highlighting its potential to streamline procurement through an electronic catalog system similar to online shopping. The primary objective is to evaluate the effectiveness and efficiency of e-purchasing in enhancing procurement operations while maintaining accountability and transparency. Utilizing qualitative data gathered from institutional records, the study assesses the current state of e-purchasing implementation and its impact on the procurement process. The findings reveal that, although UIN Walisongo has adopted e-purchasing, the scale of its implementation remains modest in terms of budget and workload. However, there has been a consistent increase in its utilization over the years, indicating a positive trend toward broader acceptance. Despite this progress, the study emphasizes the need for further improvements in the e-purchasing model to maximize its benefits. The implications of this research suggest that enhancing user training, upgrading technological infrastructure, and fostering greater stakeholder engagement are crucial steps toward optimizing the procurement process. Overall, this study contributes to the growing body of literature on e-purchasing in public sector procurement, providing insights that may inform policy and practice in similar institutions